High IL-10 mRNA levels in regional lymph nodes of colon cancer patients indicate poor prognosis - Mohamed, Alaa; Ismail, Hager; Zahran, Faten; Zein, Nabila; Lindmark, Gudrun; Hammarström, Marie-Louise; Hammarström, Sten; Sitohy, Basel (Frontiers in Immunology, 2025)
IntroductionThe prognostic value of determining mRNA levels of two markers for regulatory T cells, IL-10 and FoxP3, in lymph nodes (LNs) and primary tumors of colon cancer (CC) patients receiving curative surgery was investigated.MethodsmRNA levels were determined by real-time qRT-PCR in 370 LNs from 120 CC patients representing all four TNM stages, 66 primary tumors, 30 normal colon tissue samples and appropriate cell lines. Protein expression was analyzed by immunohistochemistry. Patients were followed for 12 years.ResultsHigh levels of IL-10 mRNA in LNs were associated with poor prognosis with shorter mean survival time of 10 and 32 months (p = 0.001 and p = 0.004) at 5- and 12-year follow-up with hazard ratios of 12.4 and 6.3, respectively. No association between IL-10 level and prognosis was seen in the primary tumor. High levels of FoxP3 mRNA were associated with good prognosis, both in LNs and primary tumor. The difference in survival time was, however, small. Analysis of IL-10 mRNA in combination with LGR6 or CXCL17 mRNA in LNs generated patients with different risk of recurrence – low-, high- and very high risk. Immunohistochemistry identified IL-10 and FoxP3 positive cells located at the outer rim of tumor aggregates.ConclusionLevel determinations of IL-10 mRNA in LNs are useful for prediction of outcome for CC patients after curative surgery. Low levels indicate that the patients do not require further treatment, while IL-10 in combination with LGR6 or CXCL17 can be used to identify patients at very high risk of recurrence.